Pengaruh Social Media Marketing TikTok, Fashion Lifestyle, dan Price Competitive Terhadap Purchase Intention dan Buying Decision Thrifting Shop - solihatul jannah; Sulhan, M.; Rahmawati, Antin (Journal of Economic, Management and Entrepreneurship, 2024)
This study aims to examine the influence of TikTok Social Media Marketing, Fashion Lifestyle, and Price Competitiveness on Purchase Intention and Buying Decision among Thrifting Shop consumers, with a case study on the TikTok account @moy_outfit. The research employs a quantitative method with data collected through questionnaires distributed to 60 respondents who are followers of the TikTok account. The data analysis technique used is Partial Least Square (PLS), a variance-based path analysis method that allows simultaneous testing of measurement and structural models. The results reveal that TikTok Social Media Marketing has a positive and significant effect on Purchase Intention with a probability significance value of 0.010 (p < 0.05). Fashion Lifestyle also has a significant influence on Purchase Intention with a probability significance value of 0.019. However, TikTok Social Media Marketing does not significantly affect Buying Decision with a significance value of 0.419. In contrast, Fashion Lifestyle and Price Competitiveness have significant effects on Buying Decision, with significance values of 0.022 and 0.000, respectively. Purchase Intention also significantly influences Buying Decision with a significance value of 0.000. These findings show that marketing on social media, especially the TikTok platform, lifestyle and competitive prices are important factors in increasing consumer purchasing intentions and purchasing decisions for thrift products.